Incidence of Sudden Cardiac Death in a Young Active Population. Issue 6 (11th June 2015) - Farioli, Andrea; Christophi, Costas A.; Quarta, Candida Cristina; Kales, Stefanos N.
Abstract : Background: Little is known about the burden of sudden cardiac death (SCD) among active, presumably healthy persons. We investigated the incidence of SCD among US male career firefighters. Methods and Results: All on‐duty SCDs among US male career firefighters between 1998 and 2012 were identified from the US Fire Administration and the US National Institute for Occupational Safety and Health databases. Age‐specific incidence rates (IRs) of SCD with 95% CIs were computed. A joinpoint model was fitted to analyze the trend in IR and to help estimate the annual percentage change of SCD rates over the years. The effects of seasonality were assessed through a Poisson regression model. We identified 182 SCDs; based on 99 available autopsy reports, the leading underlying cause of death was coronary heart disease (79%). The overall IR was 18.1 SCDs per 100 000 person‐years. The age‐specific IRs of SCD ranged between 3.8 (for those aged 18 to 24 years) and 45.2 (for those aged 55 to 64 years) per 100 000 person‐years. The annual rate of SCD steadily declined over time (annual percentage change −3.9%, 95% CI −5.8 to −2.0). SCD events were more frequent during January (peak‐to‐low ratio 1.70; 95% CI 1.09 to 2.65). In addition, the IR was 3 times higher during high‐risk duties compared with low‐risk duties. IRs among firefighters were lower than those observed among the US general population and US military personnel. Conclusions: SCD risk in this active working population is overestimated using statistics from the general population. To address public health questions among these subpopulations, more specific studies of active adults should be conducted.